1982
DOI: 10.1042/cs0630381
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxaluria in Idiopathic Calcium Stone Disease: Further Evidence of Intestinal Hyperabsorption of Oxalate

Abstract: 1. Seventeen healthy controls and 63 patients with idiopathic calcium stone disease of the urinary tract were investigated for urinary calcium and oxalate excretion and for [14C]oxalate intestinal absorption. 2. Under comparable controlled dietary intake a significant increase in calcium excretion as found in patients with stone disease. Oxalate excretion and [14C]oxalate intestinal absorption were mildly but not significantly increased. When patients with stone disease were subdivided into normocalciuric and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
1

Year Published

1986
1986
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(17 citation statements)
references
References 19 publications
2
14
0
1
Order By: Relevance
“…The low variability of the mean reference oxalate output (Table 1) confirms that none of the volunteers were stone formers as these people would excrete significantly higher levels of oxalate in their urine (Marangella et al, 1982). The low variability of the mean oxalate output suggests that the volunteers avoided other oxalate containing foods as requested.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The low variability of the mean reference oxalate output (Table 1) confirms that none of the volunteers were stone formers as these people would excrete significantly higher levels of oxalate in their urine (Marangella et al, 1982). The low variability of the mean oxalate output suggests that the volunteers avoided other oxalate containing foods as requested.…”
Section: Discussionmentioning
confidence: 89%
“…Most studies show a peak in oxalate absorption after 1 -6 h in normal subjects following ingestion of oxalate containing food (Barilla et al, 1978;Brinkley et al, 1981Brinkley et al, , 1990Marangella et al, 1982;Liebman & Chai, 1997). This indicates that there is a major uptake of oxalate from the small intestine in healthy humans.…”
Section: Introductionmentioning
confidence: 99%
“…Strong interactions between dietary Ca and dietary oxalate affecting the oxalate absorption have been described (2,(13)(14)(15)(16)(17)(18)(19) as well as denied (20). Ca supplements have been shown to lower the oxalate absorption in several reliable studies (for a review, see (21)).…”
Section: Discussionmentioning
confidence: 99%
“…High Ca in the diet as well as Ca supplements were both described as means to reduce oxalate absorption in patients (2,(13)(14)(15)(16)(17)(18)21). Interpretation of the published data as well as of our first results was hampered by the lack of information on the variation of the oxalate absorption, as well on interindividual variation as on the physiologic, intraindividual variation.…”
Section: Discussionmentioning
confidence: 99%
“…Increased dietary oxalate absorption has been implicated in the etiology of calcium oxalate nephrolithiasis both in the presence and apparent absence of intestinal disease (1)(2)(3)(4)(5)(6). Until recently most investigators had concluded that oxalate was absorbed by a passive, noncarrier-mediated pathway and that increased absorption resulted from increased passive permeability and/or increased solubility of oxalate (2)(3)(4)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%